The Indifferent, the Obedient, and the Adjusted: Three Women's Narratives about Socialism in Croatia - Potkonjak, Sanja (2012)
Paper deals with a family history and provides a personal insight into three women’s views on socialism. It simultaneously looks at the idiosyncrasies of personal female memories as against collective (male) history.
Projekt MZOS
ENG